Heavy daily alcohol intake at the population level predicts the weight of alcohol in cirrhosis burden worldwide - Stein, Eva; Cruz-Lemini, Monica; Altamirano, Jose; Ndugga, Nambi; Couper, David; Abraldes, Juan G.; Bataller, Ramon (Journal of hepatology, 2016)
[Display omitted] Studies assessing alcohol as a population level risk factor for cirrhosis typically focus on per capita consumption. However, clinical studies indicate that daily intake is a strong predictor of alcoholic cirrhosis. We aimed to identify the determinants of alcohol’s contribution to the global cirrhosis burden and to evaluate the influence of daily drinking on a population level. We performed a comprehensive analysis of the WHO 2014 Global Status Report on Alcohol and Health. We categorized countries by heavy or moderate drinking based on daily consumption, using U.S. Department of Agriculture definitions of heavy drinking. Additional data on cirrhosis cofactors were also obtained. Uni- and multivariate models were fitted to identify independent predictors of the alcohol-attributable fraction of cirrhosis. The WHO 2014 Report found that half of cirrhosis mortality worldwide is attributable to alcohol, approximating 60% in North America and Europe. In an integrative multivariate model, the designation of countries by moderate or heavy daily drinking had the strongest influence on the weight of alcohol in the cirrhosis burden. The relative contribution from alcohol increased by 11% with a transition from the moderate to heavy classification (p<0.001). Importantly, drinking patterns such as heavy episodic drinking and the type of alcohol did not independently predict the alcohol-attributable fraction of cirrhosis. Heavy daily drinking on a population level significantly influences the weight of alcohol in the cirrhosis burden. Reducing heavy drinking should be considered as an important target for public health monitoring and policies. We carried out an analysis of the WHO 2014 Global Status Report on Alcohol and Health, and categorized countries by their level of drinking (heavy or moderate). We found that half of the global cirrhosis cases, and 60% in both North America and Europe are associated with alcohol intake. We concluded that on a population level heavy daily drinking significantly influences the impact of alcohol on the cirrhosis burden.